Adolescent Addiction to Short Video Applications in the Mobile Internet Era - Lu, Lihong; Liu, Mei; Ge, Binchao; Bai, Zijin; Liu, Ziqi (Frontiers in Psychology, 2022)
The adolescent addiction to short video applications is becoming increasingly prominent, which has brought great challenges to the physical and mental health and daily life of the adolescents. This paper conducts an empirical study on the contributing factors of the adolescent addiction to short video applications based on the user generated content (UGC). Through the analysis of individual factors of the adolescent addiction from the perspective of gender, age, and family environment, this study reveals that male users are more addicted to the use of applications (APP), and such addiction varies with age, and prolonged family members’ use of short video APP can also exacerbate the adolescent addiction degree. Furthermore, through verification of the theoretical model, it indicates that UGC perception and the degree of boredom in daily life have a significant positive effect on the level of addiction to short video applications, and the degree of boredom in daily life plays a significant mediating role between them. Based on the research on the influences of UGC on the adolescent immersive experience, this study proposes a mechanism of the adolescent addiction to the use of short video applications in the mobile Internet age to provide a better service guarantee for the adolescents.